Characterization of a Novel Floral Mutation Induced by Gamma Irradiation of Philippine Rice Variety NSIC Rc9 (Apo) - Cabusora, Christopher C; Desamero, Nenita V; Borromeo, Teresita H; Buluran, Rj D; Hernandez, Jose E; Cruz, Pompe C Sta (International Journal of Sustainable Agricultural Research, 2020)
Seed mutation by gamma irradiation of 250 Gy 60Co of the Philippine rice variety NSIC Rc9 (Apo) in 2009 DS generated 390 M2 plants, from which one line exhibited a floral mutation different from those previously reported. The mutant was then designated as PR40858-SM2009DS 929-1. Floral development observation resulted in the determination of the crop stage at 76 days after seeding (DAS) in which the floral mutation started to manifest. Comparative agro-morphological characterization of the mutant in 2012 WS showed that it is variable in seven (7) traits, including floral characteristics such as, panicle axis, type and secondary branching, lemma and palea color, and seed coat pubescence. Reduction in grain yield and yield component traits was observed in the mutant line. Detailed characterization of the young panicle showed abnormalities involving the elongation of the rachis, the secondary branches, spikelet and reproductive organs. Mutations in spikelet includes reduction in size and shape, which was translated to the changes in matured grain dimensions. The mutation also affected the viability of the pollen grains resulting to higher spikelet sterility in comparison to the wildtype. The mutant were also variable in nine (9) agronomic traits, including flowering days, plant height, panicle length, tiller production, culm diameter, leaf length and width at maximum tillering, and flag leaf length and width. The characterization of the mutant line revealed other abnormalities aside from the mutation observed in its inflorescence structure making it significantly variable from the wildtype and from the other floral mutations reported in rice.